PENGARUH PROFITABILTAS DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PT UNILEVER TBK TAHUN 2022 - 2023 - Habib Muhamad; Regina Putri Kirana; Siti Nurhaliza; Gunardi; Sandy Kurniawan (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2023)
This study was carried out to assess the impact of profitability and liquidity on PT Unilever Tbk's financial results, with the aim of understanding its business performance every three months. The focus of the assessment includes capital, inventory and profit management, which can efficiently help companies avoid inappropriate decisions and improve operational efficiency. Quantitative methods are used by analyzing PT Unilever Tbk's financial report data for 2022 and the first three months of 2023 from www.unilever.co.id. Financial ratios, especially liquidity and profitability, are the main analytical tools. Performance evaluation is carried out using the time series method, identifying improvements in liquidity and profitability ratios as well as growth in company sales and profits. The results show the company's ability to fulfill both current and non-current obligations. From these findings, it is concluded that special paying attention is necessary. to factors that influence profitability and liquidity. Continuous evaluation is required to identify risks and opportunities, with improved financial performance achievable through strategic measures such as production efficiency, strong risk management, and awareness of the potential for increasing risk-related net profit margins.